team UTB-NLP at finances 2023: financial targeted sentiment analysis using a phonestheme semantic approach (2023)
Sentiment analysis in the financial domain is a challenging task that plays a crucial role in understanding public opinion, monitoring market trends, and assessing the impact of news on economic agents. In this shared task, we address targeted sentiment analysis in the financial domain, focusing on identifying the main economic target in news headlines and determining the sentiment polarity towards such targets. We propose a methodology that combines transformer-based models and phonestheme embeddings to extract meaningful features from the text, which are then used in a support vector machine (SVM) classifier for sentiment classification. Our approach shows promising results, outperforming the baseline with an F1-score of 0.529229 in Task 1. This research contributes to financial sentiment analysis by addressing the complexity of financial language and considering multiple economic agents' perspectives.